Complementarity between innovation knowledge sources: Does the innovation performance measure matter? - Ana M&#x00aa Serrano-Bedia; M&#x00aa López-Fernández; Concepción; Gema García-Piqueres (BRQ Business Research Quarterly, 2018)
We analyse complementarity between different knowledge sources (internal, external and/or cooperation) employing a wide range of innovation performance measures (product, process, organizational, and commercial). The empirical study uses 2014 Spanish CIS data and studies complementarities by performing conditional complementarity/substitutability tests. The results show evidence of conditional complementarity in product innovation performance between external and internal knowledge sources in absence of cooperation and of conditional substitute relationship between external and cooperation knowledge sources in presence of internal source. In product and process innovation performance we found a conditional substitute relationship between internal and cooperation sources when external source is used and not used, respectively. This relationship turns to conditional complementarity in organisational innovation in absence of external knowledge source. Therefore, when designing innovation strategy, managers must consider their objectives on a priority basis, since not all the strategies have the same effects on innovation performance."
Keywords: 650; Complementarity; Internal knowledge source; External knowledge source; Cooperation; Innovation performance